DAMPAK GAME ONLINE TERHADAP SIKAP SISWA BELAJAR PENDIDIKAN AGAMA ISLAM - Muhammad Iqbal (el-Moona: Jurnal Ilmu Pendidikan Islam, 2021)
Islamic religious education is the formation of changes in attitudes and behavior in accordance with the instructions of the teachings of Islam as the Prophet had done in an effort to convey the call of religion in the formation of the Muslim personality. For example, in terms of addiction to playing online games, which is currently booming, it can affect student attitudes, because online games have a decreased impact on student learning attitudes such as students being late for class, students not concentrating while studying, until they are late in collecting assignments because the time spent is more a lot to play games online. Based on this, it is very interesting to study the impact of online games. The method used in discussing this research is descriptive method. The author provides an understanding of Islamic Religious Education learning is an effort to create a condition for the creation of a learning activity with the content of Islamic teachings so that it can form morals in good virtuous students who know right and wrong so that they are able to avoid things that are not useful, especially playing online games. who can neglect the learning task of a student